Telemetry‐validated nitrogen stable isotope clocks identify ocean‐to‐estuarine habitat shifts in mobile organisms. Issue 5 (7th March 2021) - Shipley, Oliver N.; Newton, Alisa L.; Frisk, Michael G.; Henkes, Gregory A.; LaBelle, Jake S.; Camhi, Merry D.; W. Hyatt, Michael; Walters, Hans; Olin, Jill A.
Abstract: Throughout their life history, many animals transition among heterogeneous environments to facilitate behaviours such as reproduction, foraging and predator avoidance. The dynamic environmental and biological conditions experienced by mobile species are integrated in the chemical composition of their tissues, providing retrospective insight into movement. Here, we present a unique application of nitrogen stable isotope clocks ('isotopic clocks'), which integrate tissue turnover rates, consumer stable isotope ratios and habitat‐specific isotope baselines to predict time‐since‐immigration and the timing of habitat shifts in a migratory species. Nitrogen stable isotope values of blood plasma collected from juvenile sand tiger sharks Carcharias taurus, a species known to undertake seasonal movements between ocean and estuarine environments, were used to derive estimates of time‐since‐immigration and the timing of seasonal habitat shifts undertaken by this species. Nitrogen isotopic clocks estimated for 65 juvenile sand tiger sharks sampled across 6 years indicated that individual sharks predominantly arrived to estuarine habitats between June and July, with some individuals arriving as early as mid‐May. These estimates were validated by comparing isotope‐derived estuarine arrival times with those from acoustically tracked individuals. The median estuarine arrival day estimates from our isotopic approach aligned with estimates from acoustic telemetry for each sampling population. Sensitivity analyses indicated that isotopically inferred time‐since‐immigration and estuarine arrival estimates were robust to variation in isotopic turnover rate and diet tissue discrimination factors under multiple modelling scenarios. This suggests that parameterization of the nitrogen isotopic clock provides reliable estimates of time‐since‐immigration and day of arrival into new habitats if isotopic variation exists between origin and new locations. Our study presents a unique application of telemetry‐validated isotope clocks to derive retrospective estimates of time‐since‐immigration and timing of habitat shifts for animals that seasonally traverse heterogeneous environments. This approach can be readily applied across many temporal and spatial scales, and to other species and ecosystems, to facilitate rapid assessment of changes in animal habitat use and broader ecosystem structure.